2011
DOI: 10.1002/mrm.23146
|View full text |Cite
|
Sign up to set email alerts
|

Localization by nonlinear phase preparation and k‐space trajectory design

Abstract: A technique is described to localize MR signals from a target volume using nonlinear pulsed magnetic fields and spatial encoding trajectories designed using local k-space theory. The concept of local k-space is outlined theoretically, and this principle is applied to simulated phantom and cardiac MRI data in the presence of surface and quadrupolar gradient coil phase modulation. Phantom and in vivo human brain images are obtained using a custom, high-performance quadrupolar gradient coil integrated with a whol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
44
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 36 publications
0
44
0
Order By: Relevance
“…Combining nonlinear SEMs with linear gradients enables novel fast imaging strategies. One example of such a technique is localization by nonlinear phase preparation, which has been recently demonstrated by Witschey et al [30]. First in-vivo results from cardiac imaging by use of localization by nonlinear phase preparation have been reported elsewhere [31].…”
Section: Discussionmentioning
confidence: 97%
“…Combining nonlinear SEMs with linear gradients enables novel fast imaging strategies. One example of such a technique is localization by nonlinear phase preparation, which has been recently demonstrated by Witschey et al [30]. First in-vivo results from cardiac imaging by use of localization by nonlinear phase preparation have been reported elsewhere [31].…”
Section: Discussionmentioning
confidence: 97%
“…Although the proposed methods create locally linear gradient fields, these fields can also be regarded as N‐SEMs in general. N‐SEMs have proven to be useful in many aspects of both the reception and excitation phases of an imaging sequence. Therefore, increased hardware complexity is useful for many other purposes in addition to multi‐slice excitation with a single‐band RF pulse.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it has been shown that PatLoc system can be used to achieve small FOV imaging (20) and parallel transmission (21,22). However, the price to pay includes the complexity in hardware availability, control, and image reconstruction.…”
Section: Discussionmentioning
confidence: 99%